Sinemada anlatı kuramı : Pelin Esmer Sinema'sında anlatı - Yavuz, İrem (My University, 2023)
Sinema sanatının diğer sanat dallarından farklı, kendine özgü bir anlatı yapısı ve grameri vardır. Çünkü en temelde tek bir anlatı formundan ortaya çıkmaz ve görsel, işitsel, metinsel tüm anlatı formlarını içinde barındırır. Bu yüzden anlatı yapısı tüm bu formların birlikteliği ve anlamlı bir şekilde bir araya gelmesiyle oluşur. Anlatıyı oluşturan temel ögeler zaman, uzam, karakter, eylemler, olaylar, çatışma, neden sonuç ilişkisi, anlatıcının konumu ve alımlayıcının konumu olarak belirlenmiştir. Fakat sinemasal anlatı incelendiğinde bu ögelere kameranın bakış açısı da eklenmelidir. Çünkü diğer sanat dallarından farklı olarak kameranın varlığı filmin anlatı yapısını değiştiren ve belirleyen bir konumda olabilir. Bu çalışmada, bir kuram halini alan anlatı kavramı incelenecek ve sinema sanatında anlatıbilimin nasıl geliştirildiği üzerinde durulacaktır. Yeni Türkiye Sineması'nın ödüllü yönetmenlerinden Pelin Esmer'in filmleri bu çalışmanın örneklemeni oluşturacak ve filmografisinde yer alan altı filmi Koleksiyoncu (2002), Oyun (2005), 11'e 10 Kala (2009), Gözetleme Kulesi (2012), İşe Yarar Bir Şey (2017) ve Kraliçe Lear (2019) bu çalışmada incelenecek filmlerdir. Pelin Esmer filmlerine bakıldığında filmlerinin üçünün kurmaca, üçünün belgesel tarzda çekildiği görülür. Fakat kurmaca filmleri de dahil olmak üzere sinemasında gerçekliği olgusu ön plana çıkmaktadır. Gerçekliğiön plana çıkarmak adına yaptığı tüm anlatısal özelliklerin yanı sıra belgesel tarzda çektiği filmlerinde anlatıları birbirine bağlayışı bakımından kurmaca tarzdan etkilendiği görülmektedir. Aynı zamanda kurmaca filmlerinde de kamerayı kullanımında belgesel etkiler dikkat çekmektedir. Pelin Esmer Sineması incelendiğinde kurmaca ve belgesel arasında bir yerde durduğu söylenebilir ve bu tezde bunu ortaya çıkaran yapılar anlatıbilimsel olarak incelenmektedir.

The history of humanity has produced stories since its existence, and both these productions and this instinct of production have continued from generation to generation. Therefore, narratives have enclosed people since the first day of their existence. Cinema, known as the seventh branch of art, has been continuing this production in its own formal form since its existence. The art of cinema has a unique narrative structure and grammar that is different from other branches of art. Because it basically does not emerge from a single narrative form and includes all visual, auditory and textual narrative forms. Therefore, the narrative structure is formed by the coexistence and meaningful combination of all these forms. The basic elements that make up the narrative are determined as time, place, character, actions, events, conflict, cause and effect relationship, the position of the narrator and the position of the receiver. However, when the cinematic narrative is examined, the camera's point of view should be added to these elements. Because unlike other branches of art, the presence of the camera can be in a position that changes and determines the narrative structure of the film. Gerard Genette's three focus concepts on perspective are zero focus, inner focus, and outer focus; When cinematic narratives are examined, it can be revealed by the position and movements of the camera. The effect created by the camera adds value to the narrative as it determines the point of view. In this study, the concept of narrative, which has become a theory, will be examined and it will be emphasized how narratology is developed in the art of cinema. Films of Pelin Esmer, one of the award-winning directors of New Turkish Cinema, will be the examples of this study, and the six films in her filmography, The Collector, The Game, 10 to 11, The Watchtower, Something Useful and Queen Lear are the films that will be examined in this study. When we look at Pelin Esmer's films, it is seen that three of her films are fictional and three of them are documentary. However, the phenomenon of realism comes to the fore in her cinema, including her fictional films. In addition to all the narrative features she made in order to bring realism to the fore, it is seen that she was influenced by the fictional style in terms of connecting the narratives in the films she shot in documentary style. At the same time, documentary effects draw attention in the use of the camera in fictional films. When Pelin Esmer's cinema is examined, it can be said that it stands somewhere between fiction and documentary, and in this thesis, the structures that reveal this are analyzed narratically.
Keywords: Anatım; Anlatı; Anlatı Kuramı; Esmer, Pelin, 1972-; Exposition; Motion pictures; Narrative in Cinema; Narrative Theory; Pelin Esmer; Pelin Esmer Narrative; Pelin Esmer's Cinema; Sinema; Sinemada Anlatı